2018
DOI: 10.18203/2320-6012.ijrms20184215
|View full text |Cite
|
Sign up to set email alerts
|

A clinical study on nimesulide hepatotoxicity

Abstract: Background: Hepatic injury can occur with the use of nimesulide, a non steroidal anti-inflammatory drug. This study was done to evaluate the hepatic and renal functions in patients with rheumatological complaints receiving nimesulide for 2 weeks.Methods: Fifty patients with rheumatological complaints treated at orthopaedic outpatient clinic of a tertiary care centre with nimesulide 100mg twice daily were enrolled in this study. The sociodemographic details, details of comorbidities, history of use of alcohol o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…It is reported that effective delivery of nanomedicines with an adequate concentration to all malignant cells within tumors is strongly dependent on their transport properties in a hypoxia and avascular environment . However, this important challenge of delivering in anticancer therapy has received little attention, and only in recent years, microbial‐mediated biotherapy has become as an alternative approach to address this existing intricate problem . In 1890, William Coley achieved tumor regression in cancer patients by administering a cocktail of Streptococcus and other strains, collectively known as “Coley's Toxins.” This approach was thought to activate the immune system and so is considered as an early form of immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that effective delivery of nanomedicines with an adequate concentration to all malignant cells within tumors is strongly dependent on their transport properties in a hypoxia and avascular environment . However, this important challenge of delivering in anticancer therapy has received little attention, and only in recent years, microbial‐mediated biotherapy has become as an alternative approach to address this existing intricate problem . In 1890, William Coley achieved tumor regression in cancer patients by administering a cocktail of Streptococcus and other strains, collectively known as “Coley's Toxins.” This approach was thought to activate the immune system and so is considered as an early form of immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Measurement of in vivo protein turnover, synthesis, and degradation in aging and age‐related diseases has typically been performed in well‐defined model organisms in aging research such as S. cerevisiae , C. elegans , D. melanogaster , and M. musculus . Numerous studies have utilized stable isotope labeling approaches to calculate in vivo protein turnover rates in humans as well, particularly in the context of muscle protein turnover, although a few others have examined LLPs . Here, we will briefly review the experimental design, methods, and analysis tools available to perform such investigations and highlight recent methodological advances with an emphasis on the identification of LLPs.…”
Section: Protein Turnover Measurements Using Comprehensive Proteomicsmentioning
confidence: 99%
“…Isotopic labeling studies in humans are not trivial to perform: some studies have continuously infused l ‐[1‐ 13 C]‐leucine and subsequently collected skeletal muscle biopsies. It was found that aging reduced the protein synthesis rates in the skeletal muscle, which may be relevant or even causal during age‐related decline in muscle mass . Both resistance and aerobic exercise training appear to increase muscle protein synthesis and improve muscle function that may ameliorate aging effects …”
Section: Protein Turnover Analysis During Aging and Age‐related Diseamentioning
confidence: 99%